2005
DOI: 10.1002/smll.200500057
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the Charging Energy of Nanocrystal Arrays

Abstract: There is increasing research interest in assemblies of chemically synthesized nanocrystal quantum dots since the self-assembly capabilities of this class of materials offer the promise of "artificial atom" solids with unique optical, electronic, and magnetic properties. [1][2][3][4][5][6][7][8][9][10][11][12][13] From a scientific viewpoint, these systems may serve as models for understanding fundamental solid-state physical phenomena at reduced energy scales (and increased length scales) compared to conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 37 publications
0
40
2
1
Order By: Relevance
“…with the average number of nearest neighbors [23]. For hexagonally close-packed QDs, the bandwidth is simply obtained as [34] = 16 .…”
Section: )mentioning
confidence: 99%
“…with the average number of nearest neighbors [23]. For hexagonally close-packed QDs, the bandwidth is simply obtained as [34] = 16 .…”
Section: )mentioning
confidence: 99%
“…For example, a decrease of the distance between adjacent nanocrystals increases the coupling between them and yields in a decrease of the Coulomb charging energy of the individual conductive islands. Eventually, this leads to a transition from insulating to metallic behavior (Mott-Hubbard transition) [19][20][21]. Researchers have observed that in such films charging effects occur attributed to Coulomb blockade [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, superlattices consisting of metal–semiconductor nanocrystals have shown unique physical properties owing to dipole–dipole interactions, which are distinct from those of the isolated nanocrystals 3. 4 In the case of organic materials, it has been demonstrated that the thickness of thin polymer films considerably affects their physical properties, such as glass‐transition temperature, melting temperature, orientation, and crystallinity 57. However, relatively little attention has been paid to the study of the characteristics derived from the difference in size or shape of polymer nanomaterials, in contrast to metal and semiconductor nanocrystals.…”
Section: Introductionmentioning
confidence: 99%